Drawpoint spacing in block/panel caving - Castro, R.; Gómez, R. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
The design of the production level depends directly on the layout of drawpoints which must be configured primarily to ensure both level stability and high productivity. In recent years, an increase in drawpoint spacing has been observed, driven mainly by the need for greater stability and reduced development times and costs. However, design methodologies have not evolved at the same pace, resulting in a gap between traditional approaches and the conditions encountered in primary rock at the greater depths where most modern caving operations are now developed. To address this gap, the present study proposes a new drawpoint spacing design methodology that incorporates the knowledge and insights generated in block and panel caving over the past decade including physical modelling, simulations and observations of markers at the field. The methodology presented here provides an updated and practical design tool aligned with the geological and operational environments characteristic of contemporary caving mines.